Viewpoints and Perspectives of Batak Migrants on Dalihan Na Tolu: The Exposition Revition - Iskandarsyah Siregar (Lakhomi Journal Scientific Journal of Culture, 2022)
The philosophy of life of the Batak tribe, namely Dalihan Na Tolu, is believed to be able to maintain order in the social life of the Batak community and family. Dalihan Na Tolu determines the form of greeting, position and attitude that applies in traditional ceremonies and daily life. Amid the rapid current flow of globalization, there are fears that the local wisdom of traditional culture, including the philosophy of life that has been believed for a long time, will erode, especially among families living in metropolitan cities whose infiltration or infiltration. The mixing of cultures is very dynamic and robust. This research was conducted to reveal how the Batak community in the metropolitan city perceives the values of Dalihan Na Tolu. The study shows that among the Batak settlers in Jakarta, the value of Dalihan Na Tolu is still highly understood, accepted, and appreciated, even though the breadth of knowledge and depth of meaning is different. Some factors that influence these differences include sub-ethnic origin, profession, the intensity of the Batak community association, and position in the family. The study's results also concluded that the childhood environment had a significant effect on the internalization of cultural values.